Estimation of Excitation Capacitance Requirement of an Isolated Multi-phase Induction Generator for Power Generation - Alok Kumar Mohanty; K B Yadav (Institute of Advanced Engineering and Science, 2016)
Self Excited induction generators are used in remote places for electrical power generation from both conventional as well as non-conventional sources. An Induction generator can operate as a capacitor excited machine provided the machine is driven beyond synchronous speed and a suitable capacitor is connected across its terminals. In this paper a technique has been proposed to estimate the values of excitation capacitances to maintain desired terminal voltages in a multi-phase induction generator. A mathematical model using nodal admittance technique of a six-phase induction generator has been analyzed. Genetic algorithm technique is applied here to obtain the unknown parameters and the capacitance requirements to obtain desired terminal voltages under various operating conditions.